Sintesa dan Karakterisasi Biokomposit Material dari Biodegradable Polimer Poly L-Lactic Acid (PLLA) dan Selulosa - Mayang Ayudhawara Subaghio; Hikmatun Ni`mah; Prida Novarita T; Sumarno Sumarno (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Biodegradable biocomposites films made from a mixture of poly (L- lactide acid) (PLLA) and MCC (microcrystalline cellulose) with a weight ratio of MCC 0%;2.5%;5%;7.5%; and 10% by using solvent blending techniques. The aim of this study is to investigate the effect of MCC addition on the transparency, dispersion, thermal stability and mechanical properties of biocomposite products. The transparency of biocomposite films decrease with the addition of MCC filler dispersed in the PLLA matrix. The SEM results show that the more filler addition the more PLLA matrices that are filled by filler. Thermogravimetric analysis showe that the addition of MCC increase in thermal stability of biocomposites film. Most stable biocomposite film is reached by the composite with MCC content of 5 wt% with Tonset 309,35oC. Mechanical tests on biocomposite test include tensile strength and elongation at break. The value of tensile strength of biocomposite films decrease with the increasing MCC content, the highest value of tensile strength is 39 Mpa which is for neat PLLA. The elongation at break in the biocomposite films decrease with the addition of MCC, the highest value of elongation at break is 11% which is for neat PLLA